PATIENT REGISTRATION USING PHOTOGRAMMETRIC SURFACE RECONSTRUCTION FROM SMARTPHONE IMAGERY - O. Hellwich; A. Rose; T. Bien; C. Malolepszy; D. Mucha; T. Krüger (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2016)
In navigated surgery the patient’s body has to be co-registered with presurgically acquired 3D data in order to enable navigation of the surgical instrument. For this purpose the body surface of the patient can be acquired by means of photogrammetry and co-registered to corresponding surfaces in the presurgical data. In this paper this task is exemplarily solved for 3D data of human heads using the face surface to establish correspondence. We focus on investigation of achieved geometric accuracies reporting positioning errors in the range of 1 mm.